Poésie amphibie : le double état du poème - Christophe Imperiali (Itinéraires)
If we accept that a poetic text becomes a poem at the precise moment when the aesthetic relationship between this text and someone who receives it is established, we can then ask a seemingly simple question: where do we find this “poem”? Is it confined to the space of the page, where it meets the eye, or does it rather occur in the time of its diction? The aim of this article is not to decide in favour of one or the other of these answers, but to consider the generally implicit links between the material ways in which texts are transmitted and the very idea of poetry or literature. A few historical examples of the relationship between orality and writing are used here to prepare the ground for the questioning of more recent practices: those triggered by the emergence of sound recording at the beginning of the 20th century. When an author fixes a sonorous variant of a poem that he has also published on paper, how can we consider the relationship between these two states of the text? Does one of the two prevail over the other? According to what criteria? If such questions invite us to reconsider the strongly graphocentric paradigm that predominates in our cultural field, my aim, however, is not to downgrade the written word in favour of a supposedly rediscovered orality. The answers I have outlined tend towards the idea of the constitutive duality of the poem, of an “amphibious poetry”.